Representation of Child Exploitation in the Film 'Trade of Innocents' and Reflections for Indonesia - Tamba, Wahyu Pratama; Soekarni, Muhammad; Ferezagia, Debrina Vita (Asean Social Work Journal, 2025)
The film Trade of Innocents (2012) presents an overview of the situation of child trafficking in Cambodia. It explores the psychological impact of victims and the role of social support interventions in victim recovery, as well as strategies in the context of tackling child trafficking in Indonesia. The research also examines the potential strengths of the characters and protagonists in the film who demonstrate perseverance in the face of challenges. This research offers a new perspective in analyzing the issue of child trafficking, its psychological impact, social support for victim recovery, and the utilization of potential strengths. A qualitative approach was used in this research, with the type of content analysis method, supported by various sources such as previous research, books, national regulations, and international conventions on children's rights. The results concluded the complexity of human trafficking and the need for attention from various parties including the state, community, and family. The strengths perspective focuses on the strengths in the problem of human trafficking, including the strength of the main character, the ability of survivors to overcome their trauma, the role of social workers, NGOs, and the government in providing interventions to handle of child trafficking. Multi-stakeholder cooperation is needed in addressing the issue of child trafficking, advocacy, and building collective public awareness.